Mental Health Through the COVID-19 Quarantine: A Growth Curve Analysis on Italian Young Adults - Parola, Anna; Rossi, Alessandro; Tessitore, Francesca; Troisi, Gina; Mannarini, Stefania (Frontiers in Psychology, 2020)
Introduction. Health emergencies, such as epidemics, have detrimental and long-lasting consequences on people’s mental health, which are higher during the implementation of strict lockdown measures. Despite several recent psychological researches on the COVID-19 pandemic highlighting that young adults represent a high risk category, no studies specifically focused on young adults’ mental health status have been carried out yet. This study aimed to assess and monitor Italian young adults’ mental health status during the first four weeks of lockdown through the use of a longitudinal panel design. Methods. Participants (n=97) provided self-reports in four time intervals (1-week intervals) in one month. The Syndromic Scales of Adult Self Report 18-59 was used to assess the internalizing problems (anxiety/depression, withdrawn and somatic complaints), externalizing problems (aggressive, rule-breaking and intrusive behavior) and personal strengths. To determine the time-varying effects of prolonged quarantine, a growth curve modeling will be performed. Results. The results showed an increase in anxiety/depression, withdrawal, somatic complaints, aggressive behavior, rule-breaking behavior, and internalizing and externalizing problems and a decrease in intrusive behavior and personal strengths from T1 to T4. Conclusions. The results contributed to the ongoing debate concerning the psychological impact of the COVID-19 emergency, helping to plan and develop efficient intervention projects able to take care of young adults’ mental health in the long-term.